Covalent crosslinking of angiotensin II to its binding sites in rat adrenal membranes. - Paglin, S (1982)
To identify the molecular components of the angiotensin II (AII) receptor in the adrenal cortex, we have covalently linked 125I-labeled AII (125I-AII) to its binding sites by using the chemical crosslinker disuccinimidyl suberate. Membrane fractions from rat adrenal tissue were incubated with 125I-AII, washed, and treated with disuccinimidyl suberate. NaDodSO4/polyacrylamide gel electrophoresis carried out under reducing conditions followed by autoradiography showed that a major polypeptide(s) with an average Mr of 116,000 was covalently tagged with 125I-AII. Proteins with Mr of 54,000 and 45,000 were also lightly labeled. Labeling of the Mr 116,000 species was specific in that it could be abolished by prior incubation of the membranes with [Sar1,Leu8]AII or unlabeled AII. Labeling of the smaller proteins was less affected by prior incubation with [Sar1,Leu8]AII. Experiments in which crosslinking was carried out in the presence of a variety of protease inhibitors indicated that the Mr 116,000 species is not an enzyme involved in AII degradation. Gel electrophoresis under nonreducing conditions showed that this component is not derived from larger disulfide-linked entities. We suggest that the Mr 116,000 moiety is a part of the receptor system for AII. The relationship, if any, of the Mr 54,000 and 45,000 peptides to the AII receptor remains unknown.